Accuracy of intraoral scanner on subgingival finish line with gingival retraction - Damanik, Nabilah F.; Haslinda Z. Tamin; Putri WU. Ritonga (Indonesia Prosthodontic Association, 2025)
Background: The development of intraoral scanner (IOS) technology has brought about a significant transformation in dentistry, enabling more efficient and accurate digital workflows. Studies show that IOS provides clinically acceptable accuracy similar to conventional methods, especially for fixed prothesis. However, there are special challenges when impression subgingival finish line accurately. The use of gingival retraction methods is essential for easy access to these margins. Objectives: This literature review aims to describe the accuracy of IOS in impression subgingival finish line with the aid of gingival retraction, and compare the effectiveness of mechanical and chemical retraction methods in digital impression of subgingival finish line. Mechanical methods, such as the use of retraction cord, provide stability to the sulcus but may cause discomfort and potential damage to the periodontium. Meanwhile, chemical methods using aluminum chloride-based pastes show good results in displacing gingival tissue with minimal side effects. Summary: Based on existing studies, the combined method of mechanical and chemical retraction provides the best results for impression accuracy in the subgingival area, taking into account patient comfort and quality of the final result. Thus, choosing the right retraction method can improve clinical outcomes and ensure the long-term success of digital- based prosthodontic restorations. Keywords: Subgingival finish line; gingival retraction; trueness; precision; intraoral scanner.